Gentrifizierungsforschung in Deutschland Eine systematische Forschungssynthese der empirischen Befunde zur Aufwertung von Wohngebieten - Üblacker, Jan (Verlag Barbara Budrich, 2018)
On the basis of a systematic research synthesis of empirical studies on gentrification in German cities, Jan Üblacker works on the development of the research branch. He also includes a large number of previously unconsidered qualification works and shows that their approaches and findings bring significant added value for urban research. By systematically linking theoretical concepts, methods and empirical findings on social, structural, commercial and symbolic change in residential areas, the author illustrates the far-reaching empirical relevance of gentrification in German cities, but also points out gaps in previous research on the phenomenon.